Competing Interactions of RNA-Binding Proteins, MicroRNAs, and Their Targets Control Neuronal Development and Function - Amy S. Gardiner; Jeffery L. Twiss; Nora I. Perrone-Bizzozero (Biomolecules, 2015)
Post-transcriptional mechanisms play critical roles in the control of gene expression during neuronal development and maturation as they allow for faster responses to environmental cues and provide spatially-restricted compartments for local control of protein expression. These mechanisms depend on the interaction of cis-acting elements present in the mRNA sequence and trans-acting factors, such as RNA-binding proteins (RBPs) and microRNAs (miRNAs) that bind to those cis-elements and regulate mRNA stability, subcellular localization, and translation. Recent studies have uncovered an unexpected complexity in these interactions, where coding and non-coding RNAs, termed competing endogenous RNAs (ceRNAs), compete for binding to miRNAs. This competition can, thereby, control a larger number of miRNA target transcripts. However, competing RNA networks also extend to competition between target mRNAs for binding to limited amounts of RBPs. In this review, we present evidence that competitions between target mRNAs for binding to RBPs also occur in neurons, where they affect transcript stability and transport into axons and dendrites as well as translation. In addition, we illustrate the complexity of these mechanisms by demonstrating that RBPs and miRNAs also compete for target binding and regulation.